Legal Analysis of the Expansion of the Placement of Active-Duty Military Personnel in Ministries/Agencies and Civil Service Positions - Ayub Medy Marthinus Imuly (CV. Publikasi Indonesia, 2026)
This research juridically analyzes the expansion of active of the Indonesian National Army placement in civilian positions under Article 47 of Law No. 3/2025, which raises concerns over the erosion of the 1998 Reformasi spirit that mandated civilian supremacy and strict military-civilian separation. This research aims to answer two problem formulations: first, analyzing the juridical implications of expanding the placement of active TNI soldiers in ministries, institutions, and civilian positions; and second, analyzing such expansion based on the principles of civil supremacy. The methods used are normative legal research with legislative and conceptual approaches, as well as descriptive qualitative data analysis. The results of this study show that the expansion of unconditional placement, resignation or retirement from active service is fundamentally contrary to the principles of civil supremacy and the democratic rule of law. The juridical implications are internal conflicts of norms that reduce legal certainty, the creation of dualism of legal status (military and civil), violations of the principle of meritocracy and equal treatment before the law, and threats to the independence of judicial/law enforcement institutions such as the Supreme Court and the Attorney General's Office. The reconstruction of the norms of Article 47 of the TNI Law is suggested by requiring every soldier who wants to occupy civilian positions to give up their active service status (retire or resign) for the sake of upholding the principle of one man, one job, one loyalty